Caminhos da convergência da renda agropecuária no Brasil: Uma análise a partir do processo de Markov de primeira ordem para o período de 1996 a 2009 - Valois, Isabela da Silva (2012)
The Brazilian agricultural sector has made in the period of stabilization after the Real Plan (1996-2009) a satisfactory economic dynamics, in which the level of agricultural products began an upward trend and virtually uninterrupted growth. This performance suggests that state economies are undergoing a process of catching up, which in the long run there would be a tendency for poorer economies achieve the same level of economic growth (in terms of per capita agricultural GDP) of the richest economies, setting a process of convergence to steady state. Accordingly, this paper seeks to analyze the convergence of per capita agricultural income between the states of Brazil, making sure that the dynamics of the agricultural sector had contributed to the reduction of inequalities existing interstate. To this end, it was used the first-order Markov process. The results indicate the occurrence of movements backward economies to levels of income per capita agricultural lower, indicating that the economies under review showed a trend of impoverishment, despite the global economic growth presented by the sector over the period. Among the factors that led these economies to tread a path of impoverishment, one can cite the emphasis of public policy to export crops, not covered by all the federating units of the country, which would result in the strengthening of the state economies have developed, expense of which are under development; beyond the migration of manpower for the agricultural production centers in more developed agricultural, causing the "Red Queen Effect," in which the growth of agricultural GDP does not translate into growth of income per capita in the field. However, the focus of this study is to identify the occurrence of convergence / divergence, no inferences about the causes that led to the initiation of such a movement, since these factors make room for new studies that seek to investigate them, in order to provide tools for the formulation of agricultural policies aimed at minimizing or even reversal of the causes that lead to poverty in the countryside.